The Effect of the Think Pair Share (TPS) Type Cooperative Learning Model on the Learning Achievement of Grade VIII Students at MTs Bustanul Ulum Tagangser Laok on the Subject of Sound - Astutik, Fitriyah Ika (Journal of Islamic Elementary Education, 2023)
This study aims to determine the effect of the Think Pair Share (TPS) cooperative learning model on student achievement at MTs Bustanul Ulum-Tagangser Laok on the subject of sound. The research was carried out in the even semester of the 2013/2014 academic year with the implementation time of 17 – 29 March 2014. The research method used was True Experimental Design and the sampling technique used Purposive Random Sampling. The sample in this study was class VIII-B as the experimental class and class VIII-D MTs as the control class with a total of 30 students each. The experimental class was given treatment in the form of the application of the Think Pair Share (TPS) cooperative learning model and the control class was given treatment in the form of a conventional learning model. The data collection technique is a test in the form of multiple choice of 20 questions and non-test in the form of observation sheets of student learning activities. The results obtained from this study indicate that the average post-test scores for the experimental class were higher than those for the control class, namely 82.17 and 66.67 respectively. Based on the hypothesis test on the post-test data, it is found that tcount = 4.89 is greater than ttable = 2.000 so that Ho is rejected and Ha is accepted. There is a significant influence between the Think Pair Share (TPS) type cooperative learning model and the conventional model as a comparison to class VIII learning achievement at MTs Bustanul Ulum Tagangser Laok on the subject of Sound. Based on the results of observations of student learning activities, it was shown that the experimental class obtained an average activity score higher than that of the control class, namely 76.0% and 64.2%.